EXPROPRIATION IN A MATERIAL SENSE - Prica, Miloš (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Expropriation as a legal institute is both narrower and broader than formal expropriation (expropriation in a formal sense), by which we mean a legal way for revoking or restricting the right to property in an individual legal case. Different legal institutes are formed through formal expropriation, one of which is expropriation in a material sense. On the other hand, expropriation as a legal institute is also manifested beyond formal expropriation, under the umbrella of restricting one’s private property as the result of a direct statutory regulation of individual areas of the legal order, as well as on the occasion of statutory regulation of individual legal cases in judicial and other legal proceedings. Expropriation in a material sense only exists where transformation of private property into public property occurs through expropriation in a formal sense, for the purpose of achieving a precisely defined general interest, with a possibility of returning to previous state. Return to previous state (deexpropriation) takes place at the request of the former owner if it is found that the purpose of expropriation has not been achieved. This possibility of deexpropriation is exactly the differentia specifica that separates expropriation in a material sense from other legal institutes related to expropriation in a formal sense, as well as from quasi-expropriation and other forms of seizing and restricting private property. Key words: formal expropriation, expropriation in a material sense, quasi-expropriation, expropriation as a legal institute, deexpropriation
Keywords: formal expropriation; expropriation in a material sense; quasi-expropriation; expropriation as a legal institute; deexpropriation